The Development of Multicultural-Based Islamic Religious Education Materials in Al-Qur’an and Hadith Learning to Enhance Religious Moderation - Yumarni, Asmara; Anwar, Khairul; Kristina, Epa; Marlina, Teti; Herliza, Yeti (Journal of Social Work and Science Education, 2026)
This study aims to produce multicultural-based teaching materials for the Qur’an and Hadith subject in Grade XII Madrasah Aliyah (MA) that are both feasible and effective in enhancing religious moderation. The research employed the Research and Development (R&D) method based on the Borg and Gall model. The study was conducted in five public and private Madrasah Aliyah in Bengkulu City, namely MAN 1, MAN 2, MAS Darussalam, MAS Pancasila, and MAS Ja-Alhaq. The product was systematically designed to include ten core chapters that integrate the teachings of the Qur’an and Hadith with multicultural values, the principles of Islamic moderation, and noble character as the essence of Islamic education. The findings revealed that the student book achieved a very high level of validity based on expert evaluations in content, language, and design, with an average score of 88.72% (categorized as very valid). Furthermore, student responses in both limited and large-scale trials indicated a practicality level of 90.08% (categorized as very practical), confirming that this book is feasible for use as a primary resource in Qur’an and Hadith learning. The presence of this product is expected not only to enrich teaching materials in madrasahs but also to contribute significantly to strengthening religious moderation and fostering a Muslim generation that is characterized, tolerant, and broad-minded.